Determinants of Employee Performance in Healthcare Organization: The Role of Work Environment, Workload, and Motivation - Wulandari, Alyaa Ayu Nur; Dara, Siti Ruhana (SAN Scientific, 2023)
This study aims to determine the impact of work environment, workload, and work motivation on employee performance. The study focused on employees working at a hospital in Jakarta, and data was collected through a voluntary questionnaire from 112 respondents. The analytical method used was multiple linear regression, and hypothesis testing revealed that work environment, workload, and work motivation have a combined effect on healthcare employee performance. This study provides valuable insights for decision-makers in healthcare systems, health organizations, and government agencies to enhance the quality and efficiency of health services. It also highlights the importance of maintaining a favorable work environment, including the physical environment and workload, for employee well-being.